PENGARUH FIRM SIZE DAN GOOD CORPORATE GOVERNANCE SERTA CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PADA BANK UMUM SYARIAH DI INDONESIA - Magdalena, Septiana; Yuningsih, Isna; Lahaya, Ibnu Abni (EQUILIBRIUM, 2017)
This study aims to determine the effect of Firm Size peroxided by Total Assets and Number of Employees, Good Corporate Governance peroxided by Proportion of Independent Board of Commissioners, Sharia Supervisory Board, Proportion of Independent Audit Committee, and Corporate Social Responsibility to Financial Performance as peroxided by Return on Assets at the Sharia Commercial Bank in Indonesia. This research was quantitative research with the sample Sharia Commercial Bank in Indonesia during 2011 to 2015 using purposive sampling technique, with 35 samples. Method of data management used regression analysis and SPSS tool. The results showed that Total Assets, Proportion of Independent Board of Commissioners, and Corporate Social Responsibility have a negative effect on Financial Performance as measured by ROA. The number of employees has a positive effect on Financial Performance as measured by ROA. Meanwhile, the Sharia Supervisory Board and the Proportion of Independent Audit Committee have no effect on Financial Performance as measured by ROA.